Genomic Effects of the Vitamin D Receptor: Potentially the Link between Vitamin D, Immune Cells, and Multiple Sclerosis - Lu, Ming; Taylor, Bruce V.; Körner, Heinrich (Frontiers in Immunology, 2018)
Vitamin D has a plethora of functions which are important for the maintenance of general health and in particular, the functional integrity of the immune system, such as promoting an anti-inflammatory cytokine profile and reducing the Treg/Th17 ratio. Multiple Sclerosis (MS) is a chronic, inflammatory and neurodegenerative central nervous system (CNS) disorder of probable autoimmune origin. MS is characterized by recurring or progressive demyelination and degeneration of the CNS due in part to a mis-guided immune response to as yet undefined- (CNS) antigens, potentially including myelin basic protein (MBP) and proteolipid protein (PLP). MS has also been shown to be associated significantly with environmental factors such as the lack of Vitamin D. The role of Vitamin D in the pathogenesis and progression of MS is complex. Recent genetic studies have shown that a variety of common MS-associated risk- single nucleotide polymorphisms (SNPs) are located within or in the vincinity of genes associated with the complex metabolism of Vitamin D. The functional aspects of these genetic associations may be explained either by a direct SNP-associated loss- or gain-of-function in a Vitamin D-associated gene or due to a change in the regulation of gene expression in certain immune cell types. The development of new genetic tools using next generation sequencing (NGS): e.g., Chromatin Immunoprecipitation Sequencing (ChIP-seq) and the accompanying rapid progress of epigenomics has made it possible to recognize that the association between Vitamin D and MS could be based on the extensive and characteristic genomic binding of the Vitamin D receptor. Therefore, it is important to analyze comprehensively the spatio-temporal Vitamin D receptor (VDR) binding patterns that have been identified using ChIP-seq in multiple immune cell types to reveal an integral profile of genomic VDR interaction. In summary, the aim of this review is to connect genomic effects Vitamin D has on immune cells with MS and thus, to contribute to a better understanding of the influence of Vitamin D on the etiology and the pathogenesis of this complex autoimmune disease.